Unity through Omission: Literary Strategies of Recension in Ibn al-Aṯīr’s al-Kāmil fī l-Ta⁠ʾrīḫ - Hagler, Aaron M. (Arabica, 2018)
The historical chronicle al-Kāmil fī l-ta⁠ʾrīḫ (The Complete History) of Ibn al-Aṯīr al-Ǧazarī (555/1160-630/1233) treats conservatively the existing corpus of narratives of the fitna, the first Muslim civil war (36/656-41/661). Ibn al-Aṯīr alters his main source’s accounts of troublesome moments, usually through omission, to present a universal history that serves to rehabilitate the reputation of the Umayyads without criticizing the partisans of ʿAlī. While this approach may be understood as remarkable scholarly detachment from perhaps the most contentious episode of the early Islamic narrative, in fact this narrative strategy is carefully calculated to present a past that can serve as an example for the future: one in which the disagreements that had fractured the umma were surmountable, and its unity was recoverable. Such changes, while small, had a large qualitative impact due to the narrative centrality of the fitna within the wider early Islamic narrative.